Si Dios fuese un activista de los derechos humanos - Santos, Boaventura de Sousa (Colección Estructuras y procesos. Serie Ciencias sociales., 2014)
In this work, the author focuses on the difficulties and contradictions faced by human rights when faced with movements that demand the presence of religion in the public sphere. He proposes an alliance between the different theologies of liberation existing in different religions and counter-hegemonic conceptions of human rights.